2003
DOI: 10.1074/jbc.m300528200
|View full text |Cite
|
Sign up to set email alerts
|

A Constitutively Active NFATc1 Mutant Induces a Transformed Phenotype in 3T3-L1 Fibroblasts

Abstract: The calcineurin/nuclear factor of activated T cells (NFAT) signaling pathway is best known for its role in T lymphocyte activation. However, it has become increasingly apparent that this signaling pathway is also involved in the regulation of cell growth and development in a wide variety of different tissues and cell types. Here we have investigated the effects of sustained NFATc1 signaling on the growth and differentiation of the murine 3T3-L1 preadipocyte cell line. Remarkably, we find that expression of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
146
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(157 citation statements)
references
References 55 publications
9
146
1
1
Order By: Relevance
“…Moreover, involvement of Gaq-coupled receptors as the GRP-R in the activation of NFAT and in the induction of NFATdependent genes has been described in a variety of cell types (Boss et al, 1996;Horsley and Pavlath, 2002;Liu et al, 2004). Noticeably, recent reports have proposed that NFAT proteins may play an important role in cancer, having shown a direct involvement of NFATmediated transcriptional regulation of different genes, including Cox-2 (Jauliac et al, 2002;Lara-Pezzi et al, 2002;Saurin et al, 2002;Neal and Clipstone, 2003;Holzmann et al, 2004;Yiu and Toker, 2006). As mentioned above, GRP-R and Cox-2 expression in human colon cancer cells correlates with more invasive characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, involvement of Gaq-coupled receptors as the GRP-R in the activation of NFAT and in the induction of NFATdependent genes has been described in a variety of cell types (Boss et al, 1996;Horsley and Pavlath, 2002;Liu et al, 2004). Noticeably, recent reports have proposed that NFAT proteins may play an important role in cancer, having shown a direct involvement of NFATmediated transcriptional regulation of different genes, including Cox-2 (Jauliac et al, 2002;Lara-Pezzi et al, 2002;Saurin et al, 2002;Neal and Clipstone, 2003;Holzmann et al, 2004;Yiu and Toker, 2006). As mentioned above, GRP-R and Cox-2 expression in human colon cancer cells correlates with more invasive characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that constitutively active forms of NFATc1 and NFATc2 induce two distinct phenotypes in NIH 3T3 cells; whereas NFATc1 increases their proliferation capacity and transformation (34,35), NFATc2 causes their cell cycle arrest and apoptosis (35). NFATc1 has also been shown to mediate VEGF-induced endothelial cell proliferation (36).…”
Section: Discussionmentioning
confidence: 99%
“…These bone marrow stem cells are pluripotent and capable of differentiating into several lineages such as chondrocytes, myocytes, and adipocytes in addition to osteoblasts (3). Interestingly, Cn/NFAT signaling has been shown to play a critical role in the lineage decision of stem cells to differentiate into chondrocytes, myocytes, and adipocytes (34,36,37). Indeed, the global deletion of NFATc2 in mice has been shown to increase the expression of chondrocytic-specific genes and chondrogenesis, suggesting that NFATc2 is a negative regulator of chondrocyte growth and differentiation (37).…”
Section: Discussionmentioning
confidence: 99%